2019
DOI: 10.1021/acs.jafc.8b05174
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Lipophilization of Bovine α-Lactalbumin with Saturated Fatty Acyl Residues: Effect on Structure and Functional Properties

Abstract: Bovine α-lactalbumin (α-LA) was chemically modified by the covalent attachment of fatty acid residues of different length (lauroyl, palmitoyl, and stearoyl) to modify its functional and antioxidant properties. Structural changes, functional properties, and antioxidant capacity in the pH interval between 3 and 10 were analyzed. Surface properties were improved. The esterification increased the hydrophobic interactions leading to a reduction in the solubility dependent on the incorporation ratio of the fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
(100 reference statements)
3
2
0
Order By: Relevance
“…Such observed SI decrease could be primarily due to the increased hydrophobic features of acylated SCL related to the covalent incorporation of numerous fatty acid chains, determining a reduction in charged chemical groups and the consequent possible formation of additional hydrogen bonds. Similar results have been reported by Mendoza-Sanchez et al [8] for bovine α-lactalbumin acylation. However, the highest SI was observed at alkaline pH values, both for unmodified and lipophilized SCL.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Such observed SI decrease could be primarily due to the increased hydrophobic features of acylated SCL related to the covalent incorporation of numerous fatty acid chains, determining a reduction in charged chemical groups and the consequent possible formation of additional hydrogen bonds. Similar results have been reported by Mendoza-Sanchez et al [8] for bovine α-lactalbumin acylation. However, the highest SI was observed at alkaline pH values, both for unmodified and lipophilized SCL.…”
Section: Resultssupporting
confidence: 91%
“…Table 3 reports the most recent results to be compared with the present findings obtained with SCL. A water solubility decrease similar to that reported in the present study was obtained following lipophilization of α-lactalbumin with fatty acid chloride chains longer than CAC [8], even though SCL lipophilization by CAC was found to be more effective. The improvement in SCL emulsifying properties after lipophilization was comparable to the results of other studies so that EAI value observed with SCL acylated with low CAC amounts (2 mmol/g) was almost similar to those observed using both soy protein-7S acylated with caproic acid [39] and rapeseed proteins acylated with maleic anhydride [41].…”
Section: Scl Fc (%) Fs (%)supporting
confidence: 87%
See 2 more Smart Citations
“…Until recently, changing the protein pI by chemical modification has been considered an effective method to improve the solubility of protein near the original pI [ 6 , 7 , 8 ]. The esterification reaction has blocked the carboxyl groups of the protein, so that the net positive charge of the protein increases, along with the pI, thereby causing a higher solubility of the protein in a low-pH range.…”
Section: Introductionmentioning
confidence: 99%